Does the use of Information and Communication Technology through the use of Realistic Mathematics Education help kindergarten students to enhance their effectiveness in addition and subtraction? - Zaranis, Nicholas (Preschool and Primary Education, 2017)
The purpose of this research is to answer the question if and how information and communications technology (ICT) combined with the Realistic Mathematics Education (RME) helps kindergarten students to enhance their effectiveness in addition and subtraction. Our research compares the level of mathematical competence of the students taught using our ICT oriented learning method which specifically takes advantage of Realistic Mathematics Education (RME) for the concept of addition and subtraction, as opposed to traditional teaching methodology. The study dealt with kindergarten students in the city of Crete Rethymno, who were divided into two groups (experimental and control) during the school year 2012-13. The experimental group consisted of 165 students who were taught addition and subtraction with the support of computers and RME. There were 170 students in the control group which were not exposed to the computer oriented curriculum. Students in both groups were pre-tested and post-tested for their mathematical achievement. The educational software consisted of math activities, designed following the background of realistic mathematics education and more specifically that of the learning teaching trajectory for the domain of addition and subtraction. The results of the research support a positive correlation between kindergarten children’s early numeracy competence and the integration of computers in teaching and learning addition and subtraction based on Realistic Mathematics Education.